2016
DOI: 10.12741/ebrasilis.v9i3.581
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento de cópula em Cyclocephala verticalis Burmeister (Coleoptera: Scarabaeidae)

Abstract: Resumo. O gênero Cyclocephala possui grande quantidade de espécies distribuídas nas várias regiões do Brasil, entretanto, poucos são os estudos relacionados ao comportamento de cópula, assim o presente trabalho teve como objetivo estudar o comportamento de cópula de Cyclocephala verticalis Burmeister. Com uma armadilha luminosa instalada ao lado de área de pastagens, foram realizadas coletas de adultos de agosto a setembro de 2013. Em laboratório machos e fêmeas foram mantidos em recipientes separados e ao ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(9 reference statements)
2
2
0
Order By: Relevance
“…This process is quite similar to that observed in other Cyclocephala species such as C. melanocephala, C. testaceipennis, and C. verticalis (Rodrigues et al 2014, Barbosa & Rodrigues 2016. Female selection in Scarabaeidae may be related to the recognition of male sexual maturity as in Canthon cyanellus cyanellus (LeConte, 1859) (Fávila 1988) and C. verticalis (Barbosa & Rodrigues 2016), and is might be intermediated by chemical communication (see Rodrigues et al 2019). 6).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This process is quite similar to that observed in other Cyclocephala species such as C. melanocephala, C. testaceipennis, and C. verticalis (Rodrigues et al 2014, Barbosa & Rodrigues 2016. Female selection in Scarabaeidae may be related to the recognition of male sexual maturity as in Canthon cyanellus cyanellus (LeConte, 1859) (Fávila 1988) and C. verticalis (Barbosa & Rodrigues 2016), and is might be intermediated by chemical communication (see Rodrigues et al 2019). 6).…”
Section: Discussionsupporting
confidence: 71%
“…Field observation showed that C. putrida start to flight at dusk, as other Cyclocephala species, as C. verticalis (Rodrigues et al 2010, Barbosa & Rodrigues 2016, and other phytophagous Scarabaeidae, as Anomala testaceipennis Burmeister, 1856 (Rutelinae) (Rodrigues et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the steps of the mating behavior, some female A. inconstans did not accept males for copulation, demonstrating male selection. This behavior was also observed in A. testaceipennis (Rodrigues et al 2014), Cyclocephala verticalis Burmeister, 1847 (Dynastinae) (Barbosa & Rodrigues 2016) and Leucothyreus albopilosus Ohaus, 1917 (Rutelinae) (Ferreira et al 2016).…”
Section: Discussionsupporting
confidence: 53%